Visual illusion in Contemporary Theatre décor A Study in technical Variables: سامي علي حسين (Al-Academy, 2021)
Our research deals with the role of theatrical decoration in creating visual thumbs and the effect achieved as a result in the theatrical presentation in terms of supporting the idea of centralization of the dramatic construction of the show, as the researcher emphasizes that this topic has begun with a new horizon removed many technical concepts and knowledge in the theater. Horizon knowledge and discoveries based on the structures of light and sight to achieve an existing transformation from steel to ethereal. According to these new concepts, systems other than those based on old methods of presentation have been formed.In light of this, the researcher divided his research into:First: the problem of research and the need for it. The researcher asked the problem a number of questions, the most important of which is: how does the illusion in the theater affect the phenomenon of receiving. He also set his goal of revealing the visual illusion in contemporary theatrical décor. He linked the importance of research in the fact that it benefits scholars and workers in the theatrical production industry.The researcher addressed in the second chapter (cognitive framework) the structure of illusion in theatrical decoration based on the image in the visual art is considered to be deceptive and shaded and the information is collected by the sense of sight and then treated by the brain . Where the illusion of reading the image occurs through the theoretical manipulation of the drawing of the work. In the last chapter, the researcher adopted the descriptive analytical method of reading the levels of the sample and the directing treatment and the role of visual deception in the illusion achieved in the research and his awareness of the play (Facebook) which was presented on the national stage in Baghdad in March 2011 by the preparation and directing (Imad Mohammed) and representation (Mohammed Hashem), and then reached the researcher at the end of his research to the most important results and the most prominent conclusions and sealed the list of sources and references on which he relied.